2015
DOI: 10.14710/ijred.3.1.55-64
|View full text |Cite
|
Sign up to set email alerts
|

Assessing The Current Indonesia’s Electricity Market Arrangements and The Opportunities to Reform

Abstract: Existing subsidy arrangements and institutional settings in the Indonesian electricity sector distort investment decisions and lead to higher cost. Electricity supply is characterized by natural monopoly characteristics, requiring different management by governments than sectors with more straightforward market characteristics. Many countries have undergone significant re-structuring of their electricity sectors, away from one, state owned and vertically integrated monopoly supplier to a setting whereby compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…PLN coordinates the transmission, distribution, and retail. Setyawan [18] infers that this model is hardly changed due to the restriction by the Indonesian constitution. An example in 2002 showed that an electricity law which allowed further competition of IPP in retailing was annulled by the Indonesian Supreme Court [18].…”
Section: Pln As the Sole Purchasing Agencymentioning
confidence: 99%
See 2 more Smart Citations
“…PLN coordinates the transmission, distribution, and retail. Setyawan [18] infers that this model is hardly changed due to the restriction by the Indonesian constitution. An example in 2002 showed that an electricity law which allowed further competition of IPP in retailing was annulled by the Indonesian Supreme Court [18].…”
Section: Pln As the Sole Purchasing Agencymentioning
confidence: 99%
“…Setyawan [18] infers that this model is hardly changed due to the restriction by the Indonesian constitution. An example in 2002 showed that an electricity law which allowed further competition of IPP in retailing was annulled by the Indonesian Supreme Court [18]. Based on the latest regulation, IPP can still sell electricity directly to consumers under a concession area permitted by the ministry of energy and mineral resources (MEMR).…”
Section: Pln As the Sole Purchasing Agencymentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, good governance practices and clear policy and regulation will attract private sector investment that is essential for developing and deploying renewable energy. However, Indonesia is facing several challenges that may impede renewable energy development including strong state control of the electricity sector (P. L. Joskow, 2008b), substantial fossil fuel subsidies (Bridle et al, 2018), non-competitive market structures (Dhani, 2014), lack of institutional competence (Marquardt, 2014), and serious underinvestment in the electricity sector (International Energy Agency, 2008).…”
Section: List Of Tablesmentioning
confidence: 99%
“…The Law on Electricity issued in 2002 marked the first attempt to privatise part of the country's electricity supply. However, it was later annulled by the Constitutional Court for violating the Constitution(Dhani, 2014). The revised Law on Energy issued in 2007 recognised the importance of renewable energy as a means to improve the country's energy security(Government of Indonesia, 2007).…”
mentioning
confidence: 99%